One Anterolateral Impingement Syndrome in Athletes (Journal of Pakistan Orthopaedic Association, 2024)
Introduction: Etiology of ankle anterolateral impingement syndrome is physical and clinical. Namely sublocation lateral syndrome of ankle talus and tibia ligaments manifest to chronic instability, pain and synovitis formation.Methods: Impingement syndrome investigated to form mechanic instability to athletes, thus ankle activations associated with sublocation lateral syndrome via literature evaluation.Results: Ankle impingement syndrome typically in progress resulting further ankle flexion movement enhances ankle activation. In this direction, current situation starts anterior tears of talofibular and calcaneofibular ligaments, however ankle tissues not previously obviously on ligament injury to athletes as quite lateral side performance level.Conclusion: For this information concluded etiology, anatomy, and pathology to special sublocation lateral syndrome on athletes. In reason of results rarely ankle impingement syndrome of common ankle syndromes to athletes may be further examine on ankle flexion movement.